New perspectives in Audiovisual Translation: Towards Future Research Trends (2022)
The aim of this book is to contribute to the dissemination of current research carried out by young scholars who are starting to build promising careers in the field of audiovisual translation. Although it is by no means an exhaustive collection of state-of-the-art approaches to AVT, this publication offers a carefully chosen list of research perspectives that are worth exploring in the current technologised landscape that this area of translation has become. Therefore, it represents a select yet judicious group of studies, with the added strength that the contributions presented here are not limited to academic circles, but rather offer different points of view from various angles, given the diverse profiles that characterizes the authors. Thus, each chapter deals with the subject of AVT from an academic, educational or professional perspective. As diverse as their approaches are, all the young authors who have collaborated to create this volume offer enriching perspectives that reflect the potential that AVT still has today and the prospective studies that are worth undertaking to continue enriching the field of AVT.L’objectiu d’aquest llibre és contribuir a la difusió de les investigacions actuals dutes a terme per joves estudiosos que estan començant a construir carreres prometedores en el camp de la traducció audiovisual (TAV). Encara que no es tracta d’una recopilació exhaustiva dels enfocaments més avançats en aquest sector, s’ofereix un conjunt acuradament seleccionat de perspectives d’investigació que val la pena explorar en l’actual panorama tecnificat en què s’ha convertit aquest àmbit de la traducció, estudis que tenen el valor afegit de no provenir exclusivament dels cercles acadèmics, sinó que, pels diversos perfils que caracteritzen autors i autores, representen diferents punts de vista: acadèmic, educatiu i professional. Així, tot i la diversitat dels plantejaments, s’ofereixen versions enriquidores que reflecteixen el potencial que té encara hui la TAV i els estudis prospectius que val la pena realitzar per a continuar enriquint aquest camp.
Keywords: traducció; localització; traducció audiovisual; doblatge; subtitulació; subtítols; accessibilitat; videojocs; còmics; àudio descripció; subtitulació per a sords